2017
DOI: 10.1016/j.jjcc.2016.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Indications and outcomes of excimer laser coronary atherectomy: Efficacy and safety for thrombotic lesions—The ULTRAMAN registry

Abstract: In Japan, the major indications for ELCA have been ACS and ISR. ELCA can provide a safe and effective treatment even for RT lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 25 publications
1
24
0
1
Order By: Relevance
“…Previous studies have shown the safety and efficacy of ELCA compared with manual thrombus aspiration. The Japanese ULTRAMAN registry showed that ELCA was effective and safe even for the thrombotic lesions [19]. However, previous studies have not evaluated the effects of excimer laser catheter size.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the safety and efficacy of ELCA compared with manual thrombus aspiration. The Japanese ULTRAMAN registry showed that ELCA was effective and safe even for the thrombotic lesions [19]. However, previous studies have not evaluated the effects of excimer laser catheter size.…”
Section: Discussionmentioning
confidence: 99%
“…The current techniques of CTO PCI are intrinsically distinct from conventional PCI for non-occluded vessels [3,27,28]. Although several reports have demonstrated the improvement of LV function as a result of opening an occluded artery, no reports have shown a detailed breakdown of the utilization of modern techniques of CTO PCI.…”
Section: Contemporary Techniques Of Cto Pcimentioning
confidence: 99%
“…Currently, the ELCA is used in procedures requiring appropriate tissue ablation, such as acute coronary syndromes, extensive coronary thrombosis, in-stent restenosis, saphenous vein grafts, chronic total occlusions, poorly expanded stents, and calcified lesions. [2][3][4][11][12][13][14] There are no absolute coronary contraindications for the ELCA. The main complications of ELCA are similar to those seen in other types of atherectomy.…”
Section: Discussionmentioning
confidence: 99%